Income diversification and risk: Does ownership matter? An empirical examination of Indian banks - Pennathur, Anita K.; Subrahmanyam, Vijaya; Vishwasrao, Sharmila (Journal of Banking & Finance, 2012)
We examine the impact of ownership on income diversification and risk for Indian banks over the period 2001–2009. We investigate both the determinants of non-interest income and the impact of diversification on various profitability and insolvency risk measures for public sector, private domestic, and foreign banks. We document that ownership does matter in the pursuit of non-interest income. Relative to private domestic banks, public sector banks earn significantly less fee-income, while foreign banks report higher fee income. Public sector banks with higher levels of governmental ownership are significantly less likely to pursue non-interest income sources. Fee-based income significantly reduces risk, measured by profitability variables, for public sector banks. Default risk is also reduced for these banks. From a regulatory perspective, it appears that diversification benefits India’s public sector banks. Our research has implications for the changes in the risk profile for banks in emerging banking markets pursuing non-interest revenue sources.